The impact of big five personality dimensions on job performance of the employees of postal department in sri lanka - Gnanapragasam, G.K.; Sampath Kappagoda, U.W.M.R. (University of Jaffna, 2016)
The purpose of this study was to investigate the impact of big five personality dimensions on job performance of the employees of Postal Department in Sri Lanka. Job performance was considered as the dependent variable and dimensions of the big five personality model such as Extra version, Agreeableness, and Openness to experience, Neuroticism and Conscientiousness were considered as the independent variables. The sample was 91 employees in the Postal Complex of Kandy, selected according to stratified random sampling method. A questionnaire was used to collect the data from employees. The hypotheses were tested using two methods. The Pearson Product Movement Correlation Coefficient (r) for test the relationship between two variables. The unstandardized coefficient in multiple regression models also used for test the relationship between two variables. According to the results of the correlation analysis illustrated that there was a strong positive relationship between Conscientiousness and Job performance. As well as there were positive relationship between Extra version and Job performance, Agreeableness and Job performance and Openness to experience and Job performance. There is a negative relationship between Neuroticism and Job performance.
Keywords: Big five personality dimensions; Job performance